Ekstraksi senyawa tanin dalam ampas kopi sebagai sumber daya tanin terbarukan - Suhaila, Rif'ati; Husna, Zakiatul; Manurung, Renita; Siregar, Alwi Gery Agustan (Journal of Agrosociology and Sustainability, 2024)
The increase in global coffee consumption causes an increase in the amount of waste. One of the components of coffee grounds waste that is thrown into the environment is tannin. Tannins are applied in various industries, including the textile, pharmaceutical, cosmetic and food industries. The research aims to observe the effect of temperature and extraction time on tannin content using the ultrasonic extraction method. Extraction was carried out using 80% ethanol solvent with 2 variations, namely, variations in extraction temperature (40, 45, 50, 55, and 60) ˚C and extraction time (10, 20, 30, 40, 50, and 60) minutes. Extracts containing tannins were then analyzed qualitatively and quantitatively. Tannin levels were tested qualitatively using FeCl3 and Gelatin, and quantitative analysis was carried out using a UV-VIS Spectrophotometer. The functional groups contained in the tannin extract were tested using the FTIR (Fourier Transform Infra Red) Spectroscopy method. The highest tannin content was obtained at an extraction temperature of 55°C and an extraction time of 10 minutes, amounting to 215.85 mg/g-1. The tannins contained in coffee grounds extract are condensed tannins.